A Review of Concrete Properties Modified By Microbial Induced Calcite Precipitation (MICP) - Salman Rais, Mohd; Ahmad Khan, Rizwan (International Journal of Engineering and Technology, 2018)
In recent times, concrete is a vital material in the development enterprises because of its huge commitment towards quickened progress. Concrete is one among the most important resources of CO2 emission and is not considered as sustainable material. Micro cracks are natural and unavoidable in concrete. This opens the path for entry of aggressive chemicals inside concrete leading to deterioration and there arises the need for concrete to be rehabilitated. Microbial induced calcite precipitation (MICP) has proved to be a promising solution in remediating cracks in concrete by way of sustainability. The MICP technology has been studied over last few years to enhance concrete properties. Earlier research at the modes of utility of this innovative technology and subsequent picks up in strength and quality of concrete has been condensed in this paper.Â Â
Keywords: Concrete strength; durability; Microstucture; MICP; Self healing; bacteria and calcite precipitation.